Effect of Strain Rate on Tensile Fracture Behaviour of Viscoelastic Matrix (EPOXY) and Fiber Reinforced Composites - Mohamed Jaleel, Saad; Yahya Rzayeg, Arz; Ibrahem Hassan, Mashaan (Anbar Journal of Engineering Sciences, 2008)
Viscoelasticity, as its name implies, is a generalization of elasticity and viscosity. Many industrial applications use viscoelastic matrix with reinforcement fiber to obtained better properties. Tensile testing of matrix and one types of fabric polyamide composites was performed at various loading rates ranging from (8.16* 10-5 to 11.66 * 10-5 m/sec) using a servohydraulic testing apparatus. The kind of reinforcement, random glass fiber (RGF), and the kind of matrix, epoxy (E) are used shown that the linear strain (،ـ 0.5) for the three parameter model gives a good agreement with experimental results. The results showed that both tensile strength and failure strain of these matrices and composites tend to decrease with increase of strain rate. The experimental results were comparison with numerical results by using ANSYS 5.4 program for simple study case has shown some agreement. Fracture regions of the tested specimens were also observed to study micro mechanisms of tensile failure.